Strategic spatial planning in a situation of fragmented local government: The case of France. - Demazière, Christophe (Routledge, 2018)
Strategic spatial planning has been redefined by urban theorists as a collective effort to reimagine a metropolis, giving way to the coordination of public policies and private actors' strategies. But strategic spatial planning does not take place in an institutional void. This paper examines how reforms of the planning system in order to make plans more strategic intersect with reforms of local government (amalgamation, demise, grouping). The case examined is France, a country with extreme fragmentation of municipalities. In France, significant planning system reforms have been carried out in the last two decades, promoting new spatial scales and new methods for planning for sustainable territorial development. But how do these reforms work in practice in a country where planning has been decentralised to municipalities? To what extent do strategic plans make the relationship between economic growth and the protection of the environment less antagonistic? Behind a common rhetoric, there seems to be a great heterogeneity of plans regarding sustainability. This is illustrated by two case studies of growing city-regions: Rennes and Tours. We argue that the quality of intermunicipal cooperation has the greatest influence on an integrative approach to economic development within spatial planning.
Keywords: Raumplanung; Raumordnung; Landesplanung; Planungssystem; Zentralität; Kommunalverwaltung; Regionalpolitik; Strategische Planung; Fragmentierung; Zuständigkeit; Planungsebene; Territoriale Kohäsion